West African Youth Challenges and Opportunity Pathways - McLean, Mora L. (Gender and Cultural Studies in Africa and the Diaspora, 2020)
This open-access edited collection, focusing on Ghana and Nigeria, offers a transatlantic, transnational exploration of barriers that threaten the wellbeing of West African youth-ranging from Black immigrant youth in the American city of Newark, New Jersey, to students in Almajiri Islamic schools in Northern Nigeria. Incorporating themes of migration, vulnerability, and agency and aspirations, the book conveys the resilience of African youth transitioning toward adulthood in a world of structural inequality. It thus crosses the academic divide between Youth Studies and African Studies, while challenging conventional framings of Black youth as deficient and deviant-positing instead their individual and collective creativity and assets. The contributors employ different methodological approaches, including field research and autoethnography, from varying multidisciplinary and practitioner perspectives.